Relative Value of Restaging MRI, CT, and FDG-PET Scan After Preoperative Chemoradiation for Rectal Cancer. Issue 3 (March 2016) - Schneider, Daniel A.; Akhurst, Timothy J.; Ngan, Samuel Y.; Warrier, Satish K.; Michael, Michael; Lynch, Andrew C.; Te Marvelde, Luc; Heriot, Alexander G.
Abstract : BACKGROUND: Management of rectal cancer has become multidisciplinary and is driven by the stage of the disease, with increased focus on restaging rectal cancer after neoadjuvant therapy. OBJECTIVE: The purpose of this study was to assess the relative impact of restaging after preoperative chemoradiation with FDG-PET scan, CT, and MRI in the management of patients with rectal cancer. DESIGN: This was a retrospective study from a single institution. SETTINGS: This study was conducted at a tertiary cancer center. PATIENTS: A total of 199 patients met the inclusion criteria: patients with rectal adenocarcinoma; staged with positron emission tomography, CT, and MRI; T2 to T4, N0 to N2, M0 to M1; treated with neoadjuvant chemoradiation 50.4 Gy and infusional 5-fluorouracil; and restaged 4 weeks after chemoradiation before surgery between 2003 and 2013. MAIN OUTCOME MEASURES: Comparisons of the tumor stage among different imaging modalities before and after neoadjuvant chemoradiation were performed. The impact of restaging on the management plan was assessed. RESULTS: The stage at presentation was T2, 8.04%; T3, 65.33%; T4, 26.63%; N0, 17.09%; N1, 47.74%; N2, 34.67%; M0, 81.91%; and M1, 18.09%. Changes in disease stage postneoadjuvant chemoradiation were observed in 99 patients (50%). The management plans of 29 patients (15%) were changed. The impact of each restaging modality on management for all of the patients was positron emission tomography, 11%; CT, 4%; and MRI, 4%. In patients with metastatic disease at primary staging, the relative impact of each restaging modality in changing management was positron emission tomography, 32%; CT, 18%; and MRI, 6%. LIMITATIONS: This study was limited by its single-center and retrospective design. Operations were performed 4 weeks after restaging. CONCLUSIONS: Changes in the extent of disease after long-course chemoradiotherapy result in changes of management in a significant percentage of patients. Positron emission tomography has the most significant impact in the change of management overall, and its use in restaging advanced rectal cancer should be further explored.